CLIMATE PROJECTION OVER INDONESIA BASED ON THE TOTAL FOSSIL FUEL CO2 EMISSION PREDICTION USING THE BOX-JENKINS ARIMA MODEL (PROYEKSI IKLIM WILAYAH INDONESIA BERDASARKAN PRAKIRAAN EMISI CO2 DARI PENGGUNAAN BAHAN BAKAR FOSIL MENGGUNAKAN MODEL ... - Eddy Hermawan (Agromet, 2009)
This paper mainly discusses about the development of estimation models raising the rate of gas emissions of carbon dioxide (CO2) as the main parameters of global warming in Indonesia. This is important to remember not many comprehensive scientific study which shows that the impact of global warming has actually experienced by Indonesia. Using Box-Jenkins method and the stage of identification, assessment, and testing, then the best prediction model obtained for the above data, the model of ARIMA (8,1,3). This means that the predicted value for the next year depending on the data before and 8 years 3 years earlier error. In the validation data with predicted results, the MAD (Mean Absolute Deviation) is relatively high. However, the pattern of results followed the pattern predicted almost the original data with a correlation value of 99%. Based on this result, we can estimate the climate projection over Indonesia, especially during 2012-2014.